(3efaQLIs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3GdTOI eG hQOJ HGdegL jGQH YLd HGdaQL hGdCfaS CVMJ ai MQL hHjOc jaQL s
(3BNQgG (B:s
(3heGd GdeGd hMGd GdMGd hGdOjf YRjR ai HgL jG QH Hge hHGdge YLd HGdfUQ eY GdaQL JeJ hced GdhQO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3hQO GdZRGdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs